Tracking Healthy Days — A Window on the Health of Older Adults - David G. Moriarty; Rosemarie Kobau, MPH; Matthew M. Zack, MD, MPH; Hatice S. Zahran, MD, MPH (Preventing Chronic Disease, 2005)
In collaboration with its partners in the public health and aging services communities, the Centers for Disease Control and Prevention (CDC) Health Care and Aging Studies Branch has developed and validated a brief set of health-related quality of life (CDC HRQOL) measures for tracking the perceived physical and mental health of adults over time. For the past 12 years, these measures — also called the Healthy Days measures — have been used in an expanding set of population health surveys, surveillance systems, performance report cards, and evaluation studies, and they have provided useful disease and disability burden data to inform decision making and provide new insights for prevention research. Although now used continuously to assess health-related quality of life for Americans aged 12 years and older, the measures and population data have been especially valuable in applications affecting older adults, for which health-related quality of life is an outcome of primary importance. The CDC HRQOL measures are recommended to public health and social service professionals as a feasible way to assess perceived physical and mental health needs of older adults and to document the effects of policies and interventions.